If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + 450000) = 625000000 Reorder the terms: x + (450000 + x) = 625000000 Remove parenthesis around (450000 + x) x + 450000 + x = 625000000 Reorder the terms: 450000 + x + x = 625000000 Combine like terms: x + x = 2x 450000 + 2x = 625000000 Solving 450000 + 2x = 625000000 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-450000' to each side of the equation. 450000 + -450000 + 2x = 625000000 + -450000 Combine like terms: 450000 + -450000 = 0 0 + 2x = 625000000 + -450000 2x = 625000000 + -450000 Combine like terms: 625000000 + -450000 = 624550000 2x = 624550000 Divide each side by '2'. x = 312275000 Simplifying x = 312275000
| -8+z=-46 | | 3(x-22)+3(x-4)=36 | | R-35=18 | | -2x+8+7x=48 | | -2(3)(-5)(-2)=0 | | 81y^4-108y^3+24yn^3-32n^3= | | y-6-7-(y-5)+5(6y+1)= | | 100=10x-650+50 | | a+(3b-1)=2b+2 | | 8(2x-6)=2(8x+5) | | 3+7p-1=7p+22-4p | | -2x+10=28 | | -2x+10=20 | | 10-3[4(a+5)-3a]= | | -11.8x=70.8 | | 9y=-36 | | -5(2b+4)+(11b-6)=0 | | y=4E-41e^2x | | 5.1q-2.3-5.7q=-1.6q-2.9 | | g^2+6g-27=0 | | -3x+9+4x=10 | | r-13=-39 | | -(5y+2)-(-4y-8)=-1 | | 11z+9=9+11z | | (x^2+4)-(5x^2-3x+4)+(2x-3)=0 | | 8(3x-1)=2(12x+5) | | 2x+15=2x+16 | | 3+6t-2=8t+7-5t | | 84x^2+48y^2=0 | | 30=6y | | 23+(-8)+22-(-12)+8= | | (4m^2-6)(4m^2+6)= |